Third Five Year Plan Progress Report 1962-63 - Planning Commission, Government of India (Planning Commission, Government of India, 1962)
Reviewing the main developments in the Indian economy during first two years of the Third Plan, the National Council of Applied Economic Research described the period as "one of special stresses and strains". During these two years, the economic situation in the country was characterised by relatively unfavourable weather conditions and the Emergency. Although substantial advances were made in several basic branches of industry as well as in power and transport sectors, no increase was recorded in agricultural output which still contributes the largest proportionate share of national output. The first half of the Third Plan had, therefore, been a period of slow economic growth, the rise in national income being of the order of 2.5 percent per annum as compared to something over 5 per cent envisaged in the Third Plan.
Planning Commission
Planning Commission, Government of India
Keywords: Third Five Year Plan- Progress Report